2020
DOI: 10.1186/s12916-020-01726-3
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 length of hospital stay: a systematic review and data synthesis

Abstract: Background: The COVID-19 pandemic has placed an unprecedented strain on health systems, with rapidly increasing demand for healthcare in hospitals and intensive care units (ICUs) worldwide. As the pandemic escalates, determining the resulting needs for healthcare resources (beds, staff, equipment) has become a key priority for many countries. Projecting future demand requires estimates of how long patients with COVID-19 need different levels of hospital care. Methods: We performed a systematic review of early … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
436
10
24

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 556 publications
(520 citation statements)
references
References 76 publications
50
436
10
24
Order By: Relevance
“…Concerning the length of hospital stay for patients with COVID-19 disease, a systematic review done by Rees et al has suggested that LOS varies depending on multiple factors such as admission and discharge criteria, bed demand and availability, and different timing within the pandemic [ 34 ]. Death rate in our cohort was significantly increased among patients with severe CT findings, as noted in other studies [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the length of hospital stay for patients with COVID-19 disease, a systematic review done by Rees et al has suggested that LOS varies depending on multiple factors such as admission and discharge criteria, bed demand and availability, and different timing within the pandemic [ 34 ]. Death rate in our cohort was significantly increased among patients with severe CT findings, as noted in other studies [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that, a recently published systematic review of 52 studies concluded that duration of hospital stay and intensive care admission were also affected by other factors like time of epidemic and country of citizenship regardless the treatment protocol. Patients living in China had longer duration of hospital stay than other countries 69 .…”
Section: Duration Of Hospital Stay Of Hcq ± Azm Versus Standard Carementioning
confidence: 91%
“…where S = average salary per day considering the number of paid working days per week as six; Lj = average recovery time; N = Number of incident cases; P = proportion of working population, in cohort 'j'. For computation of productivity losses, the proportion of working population was considered along with an extended disability period for severe cases to account for the ICU stay [20,21].…”
Section: Valid Records 1841mentioning
confidence: 99%